PENERAPAN DALIL MUTTAFAQ DALAM PENEMUAN HUKUM ISLAM PADA HUKUM POSITIF DI INDONESIA - Miftahul Haq; Mawardi M. Saleh; Zulfahmi Bustami (Jotika English and Education Center, 2024)
The application of Positive Law in Indonesia, especially in the practice of Religious Courts, can legal discoveries still be carried out therein. The object of this research is related to the discovery of Islamic law in realizing justice based on the belief in the Almighty God, so the author uses a qualitative normative juridical research approach. The results of the research look at positive law in Indonesia, such as Law Number 7 of 1989 as most recently amended by Law Number 50 of 2009 concerning Religious Courts, and Law Number 48 of 2009 concerning Judicial Power, confirming that: Justice is carried out